A comparison between atropine and cyclopentolate in cycloplegic refraction in children - Kisten, Divashini (My University, 2019)
Background: Cycloplegic refraction is a reliable procedure for obtaining an accurate refraction in children. Atropine is considered the gold standard, however, it does not have the properties of an ideal cycloplegic agent. Theoretically, cyclopentolate is the preferred agent and many have advocated it as an alternative. In the African population where dark irides are common there is insufficient information comparing the two agents, especially so in younger aged children. Objective: To establish if cyclopentolate is as effective as atropine in cycloplegic refraction in dark irides. Method: A prospective, sequential, paired study on patients requiring cycloplegic refraction was conducted. Each patient was refracted after the usage of cyclopentolate. Refraction was then repeated 2 weeks later after using atropine. Results: 40 patients (80 eyes) were refracted with both agents. The mean difference between the agents (atropine – cyclopentolate) was +0,14 DS (95% CI: +0.05 to +0.24; paired t-test; p=0.0027), however, the effect size was small (Cohen’s d=0.35) making it clinically insignificant. No adverse effects were reported with either of the cycloplegic agents. Conclusion: Cyclopentolate is as effective as atropine for cycloplegic refraction in dark irides and can be used as an alternative to atropine for cycloplegic refraction.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine. Johannesburg, July 2019
Keywords: Bronchoscopy; Atropine; Glycopyrrolate